The Influence of Supply Chain Relationships on The Adoption of Open Standards Inter-Organizational Information Systems: A Conceptual Framework - Xiaode Pu; Felix Chan; Alain Chong (Bright Institute, 2021)
This study provides a conceptual framework to analyze where the formal and informal inter-organizational interactions influence the adoption decisions of open standards inter-organizational information systems (IOIS). Based on the Internet, open standards IOIS can help companies access to broader markets and make interfirm collaboration much easier and cheaper.In spite of these benefits, open standards IOIS have not been widely adopted by companies for external connection, which leads to questions about the importance of higher openness for inter-organizational systems. We argue that the characteristics of supply chain networks are fundamental for companies' choices of IOIS. The levels of linkages and interdependence between companies will affect how companies respond to external influences as well as heat demand for broader connection or tighter integration. Personal guanxi, the informal connections between individuals, also play an important part in companies' adoption decisions, especially in Asian countries where guanxi is prevalent business culture. Combining the different theoretical perspectives, we propose a conceptual framework and several integrative propositions for the analysis of the adoption decisions of open standards IOIS in the inter-organizational context.